That summer - Dessen, Sarah (New York : Speak, 2004)
During the summer of her divorced father's remarriage and her sister's wedding, fifteen-year-old Haven comes into her own by letting go of the myths of the past.
1020
Keywords: Sisters -- Juvenile fiction; Weddings -- Juvenile fiction; Interpersonal relations -- Juvenile fiction